PENGELOLAAN BUMDES TIMUR SEJAHTERA DI DESA UJUNG BATU TIMUR KECAMATAN UJUNG BATU KABUPATEN ROKAN HULU TAHUN 2023-2024 - Sitepu, Anjani; ,, Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This research is motivated by the suboptimal management of the Timur Sejahtera Village-Owned Enterprise (BUMDes) whose goal is to improve the village economy and optimize village assets for the benefit of the village and community. However, the management of the Timur Sejahtera BUMDes business unit still faces obstacles that result in declining profits, which also impacts the village's original income. The purpose of this study is to describe the management of the Timur Sejahtera BUMDes in 2023-2024. The research method used in this study is a qualitative approach and descriptive research. The research location was Ujung Batu Timur Village, Ujung Batu District, Rokan Hulu Regency. Data collection techniques were interviews and documentation. This study used G.R. Terry's management theory, with indicators of planning, organizing, implementing, and monitoring. The results of this study found that the management of the Timur Sejahtera BUMDes in Ujung Batu Timur Village, Ujung Batu District, Rokan Hulu Regency in 2023-2024 was not optimal due to several aspects that were not implemented well, namely organizational and supervisory aspects. From the organizational aspect, the BUMDes implementers do not understand their respective duties and functions so that the management of the Timur Sejahtera BUMDes has not yet optimally carried out its duties. Furthermore, in the supervisory aspect, there has been no supervision in the Management of the Timur Sejahtera BUMDes from 2023-2024. Keyword:Management, Supervision, BUMDes.